Customized L2 e-courses as a Shortcut to Developing Learner Autonomy and Lingua-Professional Competences of Students Majoring in Finance and Law - Elena Gavrilova; Kira Trostina; Dinara Tutaeva; Lilit Sahakyan (European Scientific Journal, ESJ, 2019)
Senior Bachelor and Master Students in economic and law universities view English for Special Purposes (ESP) course as an essential component in developing both their linguistic and vocational competences. The paper argues that reliance on the use of e-shaped professionally-relevant materials is a shortcut to professional jargon acquisition and pre-employment immersion into future job realities. The existing shortage of published ESP textbooks for students of finance and law stipulates the necessity for the teachers to develop their own customized courses tailored for particular students’ needs. Embracing the opportunities provided by information technologies and custom-built e-courses composed of autonomous e-modules has helped to create a personalized virtual learning environment for ESP students of any learning profile or academic background. In addition, it has helped in responding to the challenging contemporary labor market demands. The paper hypothesizes the paramount importance of converting selected study materials into an interactive electronic format in order to better equip students of finance and law with linguistic and professional skills. A questionnaire related to the students’ perceptions on the e-course relevance on 5-point Likert-type scale was administered to 208 bachelor and master undergraduates in Finance. This was administered after the pilot introduction of a configurable e-course at the Faculty of Distance Education in Plekhanov Russian University of Economics (PRUE), Moscow, Russia. Thus, it was also administered to 67 bachelor and master students of law and finance of Yerevan Gladzor University (YGU), Armenia. The survey concludes that tailored e-training courses get a massive student support and serve as a springboard for boosting students’ lingua-professional development and enhancing learner autonomy. However, the findings also revealed that the participants of the study even in geographically remote universities, who have quite different cultural and multicultural specificities and prefer working with the printed out paper-based version of the interactive courses, significantly outnumber (83%) those who rely solely on e-learning format (34%). The results of the study are critical to e-courses developers, university IT and administrative staff, and it also provide trajectories for further research.